Chromatophore radial muscle fibers anchor in flexible squid skin. Issue 2 (7th May 2013) - Bell, George R.R.; Kuzirian, Alan M.; Senft, Stephen L.; Mäthger, Lydia M.; Wardill, Trevor J.; Hanlon, Roger T.
Abstract Cephalopod skin is soft, flexible, and produces rapid color changes for camouflage and signaling primarily by regulating the shapes of its numerous chromatophore organs. Each chromatophore has 10–30 radial muscle cells, termed fibers, under central nervous system control. Each fiber contains myofilaments that contract in concert to stretch the pigment‐containing cell from its punctate, spherical state to a fully expanded thin disk of color. Expansion occurs in less than one second and can result in a 14‐fold expansion in pigment cell diameter. We investigated the anchoring mechanism of radial muscle fibers that expand pigment cells in the longfin squid, Doryteuthis (Loligo) pealeii. The proximal Active Zone of a radial muscle fiber adheres to the pigment cell within an ensheathing sinus. The distal portion forms terminal arbors, thereby increasing the surface area, to adhere it to the dermal extracellular matrix (ECM). While the muscle fiber is attached to the pigment cell with haptosomes, the remainder of the fiber is adhered to the surrounding basal lamina (part of the ECM) by numerous, closely spaced, small costamere‐like projections. Branching of the radial muscle fiber termini and the costamere‐like attachments are key anatomical specializations that anchor the radial muscle fibers in the pliable skin while allowing the freedom of movement required for large changes in pigment cell diameter. We postulate that these features may be relevant for the development of soft actuation models in materials science.